2022
DOI: 10.3389/fmicb.2022.820048
|View full text |Cite
|
Sign up to set email alerts
|

Strong Antimicrobial Activity of Silver Nanoparticles Obtained by the Green Synthesis in Viridibacillus sp. Extracts

Abstract: Recently, green silver nanoparticles (G-AgNPs) have gained much attention in medical science due to their extraordinary effects against multidrug-resistant microorganisms. The strong antimicrobial nature of G-AgNPs corresponds to their unique physicochemical properties such as size, shape, surface charge, and active surface groups available to interact with the pathogens. The current study demonstrates a simple, environmentally friendly, and economical method to produce G-AgNPs from an environmental isolate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 37 publications
2
39
0
Order By: Relevance
“…Pal et al [ 60 ] showed as the truncated shapes proven a better antibacterial efficacy than the spherical nanoparticles shapes because these edges can generate damages of the cell walls. Based on the information obtained from UV-VIS results the obtained nanoparticles might possibly register an antimicrobial activity due to their shape [ 27 ] but the polydispersity indicate by the shape of graphic could affect the antimicrobial effect [ 61 , 62 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pal et al [ 60 ] showed as the truncated shapes proven a better antibacterial efficacy than the spherical nanoparticles shapes because these edges can generate damages of the cell walls. Based on the information obtained from UV-VIS results the obtained nanoparticles might possibly register an antimicrobial activity due to their shape [ 27 ] but the polydispersity indicate by the shape of graphic could affect the antimicrobial effect [ 61 , 62 ]…”
Section: Resultsmentioning
confidence: 99%
“…Probably, a higher or lesser added quantity of the reducing agent lead in time, to the various morphologies and sizes with agglomeration tendency. According to the information received from DLS results the polydispersity of the obtained nanoparticles could affect the antimicrobial activity [ 27 , 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…UV-Vis, SEM, TEM, AFM, DLS, FTIR, ICPMS, and TGA studies were done as reported before [19]. For UV-Vis, SEM, TEM, AFM, DLS, and ICPMS, aqueous solutions of nanoparticles were used.…”
Section: Analytical Characterization Of Nanoparticlesmentioning
confidence: 99%
“…Comparatively, control cells show intact cells without disturbance at different scales. EDX and elemental mapping results indicated that the damage happened due to the presence of silver elements and represent a clear and sharp peak of silver [19].…”
Section: Antibacterial Activity Of P-agnps and E-agnpsmentioning
confidence: 99%